Exploring the roles of information search and information evaluation literacy and pre-service teachers’ ICT self-efficacy in teaching - Peciuliauskiene, Palmira; Tamoliune, Giedre; Trepule, Elena (International Journal of Educational Technology in Higher Education, 2022)
This study analyzes the relationship between pre-service teachers’ information search and information evaluation literacy and their information and communication technology (ICT) self-efficacy in teaching. Theoretical analysis confirmed a direct relation between information literacy and pre-service teachers’ ICT self-efficacy in teaching. However, there is insufficient understanding regarding the effect that specific components of information literacy, i.e., information search and evaluation, have on teachers’ ICT self-efficacy in teaching. Data were collected using an online survey of students in teacher training programs who were engaged as research participants. The analysis disclosed that perceived information evaluation literacy has a more strongly expressed indirect impact on teachers’ ICT self-efficacy than a direct impact, while perceived information search literacy has a stronger direct impact on teachers’ ICT self-efficacy in teaching. Therefore, for teacher educators, it is important to develop a sufficient level of information literacy and ensure a positive experience with information search and evaluation, which are related to higher pre-service teachers’ ICT self-efficacy in teaching. This finding may help support calls for teacher training and/or professional development programs with a focus on information literacy, which might increase teachers’ ICT self-efficacy in teaching and improve ICT use in teaching.